PROPERTIES AND APPLICATIONS OF ANTIFRICTION SILUMIN - E. I. Marukovich; V. J. Stetsenko (Литьë и металлургия)
Antifrictional silumin which excels traditional bronzes in mechanical and tribotechnical properties is developed. ecologically safe casting technology of billets of 30–300 mm in diameter of antifrictional silumin is created. their cost is 2–3 times lower than that of similar bronzes. the new technology is introduced in manufacture in the republic of Belarus.